West Africa workshop In Niamey (NIGER) - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
From 3 to 5 October 2013, was held in the conference room AFRICA HALL, Niamey, a regional training workshop on climate and similar "farm of the future" approach: tools to enhance the ability adaptation to climate change in West Africa.